Brinquedo: infância e contemporaneidade - Santos, Alexandre Fonseca (2018)
The purpose of this research was to understand toy meanings in its close relationship with children and childhoods in the contemporary world. A study was developed which methodology was based on bibliographical analysis based on works, articles and documents related to the topic. Added to this, a study was carried out from works that describe different conceptions of the child in different periods of history. The study showed that in today’s society there is an overvaluation of the toy as a product of priority use of children, although not all have the same access to this object. The market and media culture were identified as the main disseminators of these objects for children, who have been stimulated from an early age to exacerbated consumption. It has been observed that research on toys in Brazil has increased substantially in the last decades, covering several areas of knowledge, such as education, medicine and psychology. It was verified that the toy has a cultural, philosophical and psychological dimension and if there are common points in which these elements converge is the unanimity around the impossibility of dissociating the history of the toys with the advances and technical social transformations of the societies. Keywords: toy, childhood, contemporaneity, culture, media